Catalytic Activity of Polynuclear vs. Dinuclear Aroylhydrazone Cu(II) Complexes in Microwave-Assisted Oxidation of Neat Aliphatic and Aromatic Hydrocarbons - Sutradhar, Manas (Molecules, 2018)
One-dimensional (1D) polynuclear Cu(II) complex (1) derived from (5-bromo-2-hydroxybenzylidene)-2-hydroxybenzohydrazide (H(2)L) is synthesized and characterized by elemental analysis, IR spectroscopy, ESI-MS, and single crystal X-ray crystallography. Its catalytic performance towards the solvent-free microwave-assisted peroxidative oxidation of aliphatic and aromatic hydrocarbons under mild conditions is compared with that of dinuclear Cu(II) complexes (2 and 3) of the same ligand, previously reported as antiproliferative agents. Polymer 1 exhibits the highest activity, either for the oxidation of cyclohexane (leading to overall yields, based on the alkane, of up to 39% of cyclohexanol and cyclohexanone) or towards the oxidation of toluene (selectively affording benzaldehyde up to a 44% yield), after 2 or 2.5 h of irradiation at 80 or 50 °C, respectively.